Activation of dopamine D4 receptors within the anterior cingulate cortex enhances the erroneous expectation of reward on a rat slot machine task. (June 2016) - Cocker, P.J.; Hosking, J.G.; Murch, W.S.; Clark, L.; Winstanley, C.A.
Abstract: Using a rodent slot machine task (rSMT), we have previously shown that rats, like humans, are susceptible to the reinforcing effects of winning signals presented within a compound stimulus array, even when the pattern generated predicts a negative rather than a positive outcome such as during a "near-miss". The dopamine D4 receptor critically mediates the erroneous reward expectancy generated on such trials. D4 receptors are particularly enriched within frontal and limbic areas activated during slot machine play, such as the anterior cingulate cortex (ACC). We therefore selectively inactivated the ACC to confirm involvement of this region in rSMT performance, and subsequently examined the specific contribution of local D4 receptors. ACC inactivations generally impaired animals' ability to optimally differentiate winning from losing outcomes. Local administration of the D4 agonist PD168077 had a qualitatively similar effect, but increased reward expectancy was only evident on archetypal "near-miss" trials i.e. when the first two of three stimuli in the array were concordant with a rewarding outcome, and only the last stimulus critically signalled a non-win. These data indicate that the ACC is critically involved in parsing the appropriate response when competing stimulus–outcome associations are activated, and that signalling via D4 receptors may play a particularly important role in gating the temporal and spatial summation of salient events. Such findings provide novel insights into the mechanism underlying the erroneous expectations of reward generated when playing slot machines, and suggest a mechanism by which D4 receptor antagonists may be effective in treating gambling disorder. Highlights: On a rodent slot machine, rats share key behavioural features with human gamblers. Provides insight into cognitive biases that may contribute to gambling disorder. The anterior cingulate cortex is critically involved in differentiating wins/losses. D4 receptors within the anterior cingulate mediate attributions of salience.